Investigation and optimization of a two-stage cascade ORC system for medium and low-grade waste heat recovery using liquefied natural gas cold energy. (March 2022) - Yu, Zeting; Feng, Chunyu; Bian, Feiyu; Wang, Daohan
Highlights: A two-stage cascade ORC system for multi-grade waste heat recovery is proposed. Waste heat and liquefied natural gas cold energy are harvested simultaneously. Examined the effects of key thermodynamic and economic parameters. The combined system is optimized to achieve the best performance. Abstract: This study proposed a two-stage cascade organic Rankine cycle (ORC) to harvest the medium and low-temperature discharged heat from internal combustion engine (ICE), and a liquefied natural gas (LNG) cold energy system is integrated into the proposed cycle in order to realize the cascade utilization of ICE multi-grade waste heat more efficiently. The thermodynamic and economic models are developed to investigate the proposed system performance under steady-state conditions. The influence of the important thermodynamic parameters, e.g. the ORC turbine inlet temperature, the high pressure of first-stage ORC and the outlet temperature of condenser are investigated. The calculated results indicated that the thermal efficiency and the exergy efficiency achieved 27.31% and 33.73%, respectively. In addition, it was found that the total sum unit cost of system product was decreased by increasing turbine Ⅰ inlet pressure. Furthermore, to reach the conflicting compromise between the two aspects of thermodynamic and economic, the Non-dominated Sorting Genetic Algorithm (NSGA-II) is employed to carry out the multi-objective optimization study by which the external investment cost and the thermal efficiency are selected as the objective function. At the same time, the influence region of decision variables related to the optimization is determined according to the scatter distribution of decision variables. Moreover, the exergy destruction and the investment cost ratio of each component under the optimization conditions are analyzed to obtain the preferred performance of the key components. The findings could provide references for the ORC system design and operation driven by multi-grade waste heat.